1984
DOI: 10.1016/0042-6822(84)90033-3
|View full text |Cite
|
Sign up to set email alerts
|

Murine hepatitis virus-4 (strain JHM)-induced neurologic disease is modulated in Vivo by monoclonal antibody

Abstract: Monoclonal hybridoma antibodies directed against the polypeptides of murine hepatitis virus-4 (JHM strain) were tested for their ability to alter the course of a normally lethal intracerebral virus challenge. Three monoclonal antibodies directed against two distinct epitopes on the E2 glycoprotein of MHV-4 protected mice against lethal virus challenge and converted the infection from fatal encephalomyelitis to demyelination. A single neutralizing antibody directed against a third epitope on E2 as well as seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
153
2
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(167 citation statements)
references
References 13 publications
11
153
2
1
Order By: Relevance
“…With purified viral preparations, a non-specific background of N protein was occasionally observed when anti-E2 and anti-E3 MAbs were tested, both by Western immunoblotting and immunoprecipitation experiments. Non-specific binding to N protein was also obtained in studies with other coronaviruses (Talbot et al, 1984;Laude et al, 1986;. The N protein is the most abundant structural component of the coronavirus virion (Siddell et al, 1983).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…With purified viral preparations, a non-specific background of N protein was occasionally observed when anti-E2 and anti-E3 MAbs were tested, both by Western immunoblotting and immunoprecipitation experiments. Non-specific binding to N protein was also obtained in studies with other coronaviruses (Talbot et al, 1984;Laude et al, 1986;. The N protein is the most abundant structural component of the coronavirus virion (Siddell et al, 1983).…”
Section: Discussionmentioning
confidence: 94%
“…These data suggest that the critical antigenic determinants are probably conformation-dependent, as reported with other coronaviruses. Talbot et al (1984) found that three neutralization epitopes in MHV-JHM are sensitive to SDS denaturation, whereas in the case of transmissible gastroenteritis virus (TGEV), all six critical determinants are sensitive to SDS denaturation and 2-mercaptoethanol (Jim6nez et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not unique: this phenomenon has also been described for Sindbis virus where it appears that anti-E2 monoclonal antibodies can mediate clearance of virus from CNS cells, perhaps by restricting viral gene expression (Levine et al, 1991). In addition to alphaviruses, antibodies are important in clearing virus from the CNS or initiating restricted replication in CNS cells in a number of other infections including TMEV, reovirus, rabies virus, mouse hepatitis virus and measles virus infections (Fujinami et al, 1989;Kurtz et al, 1995;Tyler et al, 1989;Perry & Lodmell, 1991 ;Buchmeier et al, 1984;Liebert et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the relatively slowly responding B cells have been studied primarily as protectors against re-establishment of a viral infection. In accord with this protective role, B cell-derived Abs protect mice from the lethal effects of high dose MHV infection when transferred near the time of infection (11)(12)(13). However, the contrast of viral clearance in CD8 ϩ T cell-deficient mice with the lack of viral clearance in T and B cell-deficient RAG knockouts suggests that the B cell could be an additional potent viral regulator during a primary infection.…”
mentioning
confidence: 99%